2016
DOI: 10.1007/s00262-016-1936-0
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the promoter region of PD-L1 serves as a binding-site for SP1 and is associated with PD-L1 overexpression and increased occurrence of gastric cancer

Abstract: PD-L1 is a member of the B7 family co-inhibitory molecules and plays a critical role in tumor immune escape. In this study, we found a polymorphism rs10815225 in the PD-L1 promoter region was significantly associated with the occurrence of gastric cancer. The GG homozygous frequency was higher in the cancer patients than that in the precancerous lesions, which was higher than that in the health controls. This polymorphism locates in the binding-site of Sp1 transcription factor (SP1). The expression level of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
0
50
1
1
Order By: Relevance
“…On the other hand, PD‐L1 is generally produced by cancer cells to escape immune surveillance, and is a molecular target for cancer immune therapy . Previous report showed that the PD‐L1 gene promoter is regulated by DNA methylation or Sp1 binding in cancer cells . There is the possibility that ATF7IP/MCAF1 may control PD‐L1 expression via Sp1,as indicated by published ChIP‐seq data of colon cancer (Figure A).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, PD‐L1 is generally produced by cancer cells to escape immune surveillance, and is a molecular target for cancer immune therapy . Previous report showed that the PD‐L1 gene promoter is regulated by DNA methylation or Sp1 binding in cancer cells . There is the possibility that ATF7IP/MCAF1 may control PD‐L1 expression via Sp1,as indicated by published ChIP‐seq data of colon cancer (Figure A).…”
Section: Resultsmentioning
confidence: 89%
“…[41][42][43] Previous report showed that the PD-L1gene promoter is regulated by DNA methylation or Sp1 binding in cancer cells. 44,45 There is the possibility that ATF7IP/MCAF1 may control PD-L1 expression via Sp1,as indicated by published ChIP-seq data of colon cancer ( Figure S3A).…”
Section: Expression Levels Of Nuclear Atf7ip/ Mcaf1 Are Correlated mentioning
confidence: 99%
“…The single nucleotide polymorphism (SNP) rs4143815C>G in the 3 UTR of PD-L1 has been associated with an increased cancer risk and might be used as biomarker to predict the susceptibility to cancer [76]. Two polymorphisms characterized by >G changes localized in the 5 UTR of PD-L1 serve as binding site for SP1 [77] thereby affecting PD-L1 expression. Thus, variations in the PD-L1 promoter could lead to an overexpression.…”
Section: Pd-1 and Cd274 Polymorphismsmentioning
confidence: 99%
“…12 PD-L1 is expressed in a variety of cancer cells, such as prostate cancer, lung cancer, and melanoma. 16,17 PD-L1 has also been a potential therapeutic target for gastric cancers. Reportedly, the expression of PD-L1 is upregulated and associated with a worse overall survival of gastric cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, the expression of PD-L1 is upregulated and associated with a worse overall survival of gastric cancers. 16,17 PD-L1 has also been a potential therapeutic target for gastric cancers. 18 However, how PD-L1 expression is upregulated in gastric cancers remains elusive.…”
Section: Introductionmentioning
confidence: 99%